Setting as an Indicator of the Main Character's Social Status in the Film Home Sweet Loan Directed by Sabrina Rochelle Kalangie - Amarta, Dika; Abidin, Zainal (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This research aims to analyze the function of setting in signifying the social status of the main character, Kaluna, in the family drama film Home Sweet Loan (2024). The film portrays the struggles of the sandwich generation in a modern urban environment. Utilizing a qualitative descriptive method, the analysis focuses on 10 selected scenes that reflect Kaluna's social status through three elements of setting: place, time, and social context. Indicators of social status (occupation, clothing, personal belongings, and speech style) serve as the foundation for the analysis. The research concludes that setting plays a crucial role, both narratively and visually, in communicating the character's social status. The visible contrast between the simple family home, the formal office, and the modern friend’s apartment illustrates class differentiation. Despite having substantial savings, Kaluna is positioned within the lower-middle class due to asset limitations and family pressure. Her social status is categorized as achieved status, attained through hard work and strict financial management, thereby superseding her family's traditional hierarchy.